Interaction flow method for many-fermion systems - Honerkamp, Carsten; Enss, Tilman (Physical review. B, Condensed matter and materials physics, 2004)
We propose an interaction flow scheme that sums up the perturbation expansion of many-particle systems by successively increasing the interaction strength. It combines the unbiasedness of renormalization group methods with the simplicity of straightforward perturbation theory. Applying the scheme to fermions in one dimension and to the two-dimensional Hubbard model we find that at one-loop level and low temperatures there is ample agreement with previous one-loop renormalization group approaches. We furthermore present results for the momentum dependence of spin, charge, and pairing interactions in the two-dimensional Hubbard model.